113. Short-term effect of different tdcs intensities on motor cortex excitability. Issue 1 (January 2015) - Chieffo, R.; Ciocca, M.; Leocani, L.; Miranda, P.C.; Rothwell, J.
<x xml:space="preserve">Abstract</x> To evaluate the on-line and short-term effects of different intensities of anodal and cathodal transcranial direct electric stimulation (tDCS) on the human motor cortex. 14 healthy subjects received anodal and cathodal tDCS in a random order on two separate sessions using a 35 cm2 electrodes positioned over the left M1 and the contralateral supra-orbital region. During each session tDCS was randomly delivered at 0.5, 1, 1.5 and 2 mA with a wash out period of 25 min between intensities. The duration of stimulation was varied so that the total charge transferred was 4 mA.min for all intensities. Twelve motor evoked potentials (MEPs) to transcranial magnetic stimulation (TMS) were recorded from the right first dorsal interosseous muscle before (baseline), at the beginning (on line 1), at the end (on line 2) and immediately after (post) each stimulation. Data were analysed with a repeated measures ANOVA using polarity (anodal/cathodal), intensities (0.5, 1, 1.5 and 2) and time (baseline, on line 1, on line2 and post) as within subject factors. Paired t tests were used for post hoc comparisons. the ANOVA showed only a significant effect of time on MEPs amplitude (F:8.7, p < 0.001). MEPs were significantly higher during (on line 1 p = 0.001, on line 2 p = 0.002) and immediately after either polarity of stimulation (p = 0.02) compared with baseline. Short duration application of both anodal and cathodal tDCS facilitates corticospinal output during and immediately after application. The effects seem to be independent of the intensity and the duration of stimulation if the total amount of charge delivered is constant. Our findings could be, however, the result of an interaction between TMS and tDCS simultaneously delivered. Moreover we cannot exclude a sort of cumulative effect of several tDCS stimulations with a non effective wash-out period.